Measurement of acetabular wall indices: comparison between CT and plain radiography. Issue 1 (19th July 2021) - Nazaroff, Jaron; Mark, Bryan; Learned, James; Wang, Dean
Abstract: The purpose of this study was to compare measurements of anterior wall index (AWI) and posterior wall index (PWI) on computed tomography (CT) to those on radiographs (XR). A consecutive cohort of 33 patients (45 hips total) being evaluated for hip pain with both XR and CT was examined. Preoperative measurements of AWI and PWI were performed utilizing supine anteroposterior pelvic XR and coronal and swiss axial CT scans by two independent raters. Mean differences between XR and CT measurements were compared, and agreement between measurements was assessed using the concordance correlation coefficient ( rc ) and Bland–Altman analysis. A total of 39 hips in 28 patients were analyzed. The mean patient age was 31.1 ± 9.0 years, and 50% were female. Mean AWI and PWI on XR was 0.50 ± 0.14 and 0.91 ± 0.12, respectively. Measured values of AWI were consistently larger (0.08 ± 0.10, P < 0.01) on XR compared with both coronal and swiss axial CT, with moderate agreement between XR and CT measurements ( rc = 0.68–0.70). Measured values of PWI were consistently smaller (0.15 ± 0.12, P < 0.05) on XR compared with both coronal and swiss axial CT, with poor agreement between XR and CT measurements ( rc = 0.37–0.45). Measured values of acetabular wall indices on XR were consistently larger for AWI and smaller for PWI relative to CT. Agreement between XR and CT measures of the indices were moderate to poor. This highlights the need for standardization of XR- and CT-based measurements to improve assessment of acetabular coverage and subsequent clinical decision-making.